Tailored photoluminescence properties of a red phosphor BaSnF6:Mn4+ synthesized from Sn metal at room temperature and its formation mechanism. (February 2017) - Xi, Luqing; Pan, Yuexiao
Graphical abstract: A red phosphor BaSnF6 :Mn 4+ with good thermal stability has been prepared by a highly efficient strategy at room temperature and its reaction mechanism has been studied. Highlights: Synthesis of BaSnF6 :Mn 4+ at room temperature and its reaction mechanism. The phosphor shows good thermal stability and optical properties. The influence of synthesis conditions on luminescence is studied. Abstract: A red phosphor BaSnF6 :Mn 4+ has been prepared by etching Sn metal in solution including BaF2, HF, and K2 MnF6 at room temperature under continuous stirring for several hours, which is a highly efficient strategy for synthesis of Mn 4+ doped complex fluorides. The phase identification, thermal stability, and structure of the phosphor BaSnF6 :Mn 4+ have been investigated by XRD, TG-DSC, and IR, respectively. Broad and intense absorption in blue region and high thermal stability makes the phosphor BaSnF6 :Mn 4+ a competent candidate for application in InGaN – YAG:Ce type white LEDs (WLEDs) with high color rendering index (CRI). The WLED fabricated with YAG:Ce and BaSnF6 :Mn 4+ exhibits "warm" white light with CRI of 83.6 and correlated color temperature (CCT) at 3576 K, which indicates promising application in indoor solid-lighting.